SUBSTANTIATION OF ADMINISTERING DEXMEDETOMIDINE TO CATS DURING OVARY HYSTERECTOMY - Omelyanenko, O. E.; Kulynych, S. M. (Scientific Progress & Innovations, 2020)
Ovary hysterectomy is a fairly wide-spread surgical procedure nowadays. This operation is performed when pathologies are detected (pyometra, cystic neoplasms), and also to eliminate sexual desire in animals. While discussions concerning the humaneness and necessity of this procedure are continuing, it is necessary to ensure safe and high-quality surgical interventions in the clinic. The main aim in the work of the anesthe-siologist is the choice of anesthesia and premedication. The research was conducted in the veterinary clinic “Na Robochiy” in the city of Dnipro during the period of 2019–2020. The purpose of the study was to de-termine analgesic, sedative effects and to study the effect on blood morphological parameters (erythrocytes, leukocytes, hemoglobin, hematocrit, and blood platelets) of α2-adrenoceptor agonists, in particular dexme-detomidine and sedazine. 2 groups of cats, 10 animals in each, were formed for investigation. In the experi-mental group, the scheme Dexmedetomidine + Butorphanol + Propofol was used, in the control group – Sedazine + Butorphanol + Propofol. It turned out that in the experimental group the onset of anesthesia was faster than in the control by 47.6 %. Time difference was insignificant as to the duration of anesthesia – 2.4%. At the same time, the awakening period after surgery in the control group was by 87.8 % longer than in the experimental group. If we pay attention to the impact on the body's systems, in both groups after the preparation administration, decrease in blood pressure was observed, which then gradually leveled off to physiological norms. To determine the analgesic effect, blood pressure (average), heart rate, contraction of the abdominal wall muscles in 4 periods of the surgery (before surgery, during opening the white line, dur-ing the most traumatic manipulations, and the stage of recovery after anesthesia) were studied. ). It was found that in the experimental group, heart rate (in all periods of the study) averaged 133.9 beats / min., blood pressure – 114.6 mm/ mercury, and contractions of the abdominal wall muscles were barely noticea-ble during more traumatic manipulations, while the indicators of the control group were: heart rate - an av-erage of 166.9 beats / min., blood pressure – 142.5 mm/ mercury, and contractions of the abdominal wall muscles were significantly noticeable during traumatic manipulations. If we evaluate in more detail for each of the surgery periods, the heart rate in the control group during the first period was 16.8 %, the II – 18.7 %, the III – 24.4 % and during the IV – 19.3 %, which were higher than in the experimental group. At the same time, the indicators of blood pressure – 11.8 %, 26.3 %, 28.7 %, 8.8 %, were respectively, higher than in the experimental group. In the study of morphological (clinical) blood indicators, it was found that the decrease, after administering the main preparation, was observed both in the experimental and control groups: eryth-rocytes decrease was barely noticeable – about 4 % (in comparison with the control group), leukocytes – by 8.2 % (in comparison with the control group), hemoglobin - by 2.3 % (in comparison with the experimental group), hematocrit – by 13.1 % (in comparison with the control group), and blood platelets – by 26.2 % (in comparison with the experimental group). Therefore, when analyzing all the data, we can conclude that using the scheme Dexmedetomidine + Butorphanol + Propofol is more effective in terms of entering the anesthesia, obtaining a better analgesic effect, but it turned out that Dexmedetomidine and Sedazine preparations can have a strong effect on morphological blood indicators.